1994
DOI: 10.1111/j.1365-2621.1994.tb06910.x
|View full text |Cite
|
Sign up to set email alerts
|

Shear Conversion of Corn Meal by Reverse Screw Elements during Twin‐Screw Extrusion at Low Temperatures

Abstract: MATERIALS & METHODSCorn meal was extruded in a twin-screw extruder to study effects of one and two reverse-screw elements on conversion at extrusion temperatures < 60°C. Significant conversion was observed across the reverse-screw elements. The conversion was due to shear alone, since thermal effect was negligible at these low temperatures. Encompassing the reverse-screw elements were four visually distinct zones characterized by the state of the material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…That amount of conversion was achieved by tribological shearing (friction) of granules in the extruder if the moisture content in the starch feed was 35%. Yam et al (1994) analyzed materials along the screw channel after "dead-stop" of a steady state twin screw extrusion of corn meal with 20% moisture. They reported that up to conversion between 20 and 32% the material was obviously in a powdery state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That amount of conversion was achieved by tribological shearing (friction) of granules in the extruder if the moisture content in the starch feed was 35%. Yam et al (1994) analyzed materials along the screw channel after "dead-stop" of a steady state twin screw extrusion of corn meal with 20% moisture. They reported that up to conversion between 20 and 32% the material was obviously in a powdery state.…”
Section: Resultsmentioning
confidence: 99%
“…Another interesting aspect of extrusion is that, in general, more than half the extruder length contains some material in powdery state (Yam et al, 1994. Study of the interactions and frictions among powders and other surfaces is called tribology.…”
Section: Introductionmentioning
confidence: 99%
“…For example, for the waxy maize starch, granule destruction by mechanical forces can occur at much lower temperatures than those required for gelatinizing or melting the starch granule under conditions where no mechanical energy is applied [18]. Yam et al [19] reported that shear energy alone was responsible for the conversion of corn meal at low temperatures. Starch gelatinization during extrusion is crucial because it affects feed digestibility, product expansion.…”
Section: Introductionmentioning
confidence: 99%
“…These equations have been used to describe kinetics of starch cooking processes in a single screw extruder, in a capillary rheometer [10][11], and in a twin screw extruder [12]. Recently, the conversion of starch [20] rate 0 to 550 s -1 , starch conversion 0 to 0.36 (36 %), and normal pressure 0 to 83 kPa) parameter values in each functionality were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…1, Soviet Encyclopedia, Moscow 1988, p. 394. [32] M. J. Gidley: personal communication, (1995), reference quoted from[12].…”
mentioning
confidence: 99%